Rock the tech stage : how the best speakers in tech present ideas and pitch products - Santolalla, Oscar (Apress, 2020)
One impactful product launch can make a world of difference in a companys lifelong success. Unforgettable presentations, such as the iPhone launch by Steve Jobs, have set high standard for wow-ing a tech audience, and lessons can be taken from this and other memorable conference stage moments to ensure your own personal success on the stage. A few simple practices can solidify your place and help you rock the tech stage. By revealing ten essential secrets to speaking persuasively in the tech arena, author Oscar Santolalla lends his industry expertise to the lucky readers of Rock the Tech Stage. With real-world advice from entrepreneurs, executives, and engineers from companies that have shaped modern tech history, Santolalla has created an invaluable resource for those wanting to improve their presentation and demo skills. Whether you want to up your game in small team meetings or in a large-scale launch for thousands, Rock the Tech Stage is the handbook youve been looking for. As the culture changes and continues to adapt, there are increasingly more spaces to share your knowledge and promote your creations. Several unprecedented factors have changed the venues, styles, and technology behind public speaking, and whether you are speaking to a video call of ten colleagues or an arena of thousands, this book will serve as your trusted guide. How should you speak about your product or company in a way that instills long-term faith and fidelity in your audience? Rock the Tech Stage addresses all of the above concerns and so much more. No matter how large or small your project or invention may be, the tech stage that awaits you is yours for the taking, and it is up to you to seize the day and rock it.